The applicacion of mathematical model for diagnostic test while estimating student’s aerobic capacity - Kosareva, Natalja; Krylovas, Aleksandras; Tamošauskas, Povilas; Dadelo, Stanislavas (Lietuvos matematikos rinkinys, 2010)
In the paper diagnostic test creation model proposed earlier by authors is applied for creation of the test designed to esimate aerobic capacity of VGTU students. The pilot research demonstrated how the most informative test for the observed group of testees could be constructed from dichotomous diagnostics operators. The calibration procedure of fitting model parameters according to the empirical data was accomplished. The best fitting diagnostic operator was chosen from four various function classes. Probability distribution of test result and test information value were calculated according to the proposed technique. The result of the test – normed-referenced estimation of testees depending on the latent parameter (aerobic capacity VO2max). Maximum oxigen consumption was evaluated using maximum likelihood method. The proposed mixed model results were more accurate for normed-referenced estimation of aerobic capacity.